PENGARUH PEMASANGAN ANGKER UJUNG TERHADAP PERILAKU RUNTUH BALOK BETON BERTULANG DENGAN PENAMBAHAN LAPIS GFRP (Glass Fibre Reinforced Polymer) - Sudarsana, I K.; Rai Widiarsa, I B. (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009, 2009)
Some researches have shown that critical phenomena on the use of FRP sheets as external reinforcement is de-bounding between the FRP sheet and concrete. This research was done to investigate the effect of end anchorage on failure behavior and flexural strength of reinforced concrete beam with additional GFRP sheet. The test was done on reinforced concrete beam specimens with dimension of 100 x 150 x 1100 mm on a simple support having a span length of 900 mm. The specimens were loaded using 2 point concentrated loads at 300 mm from the supports. Three group specimens were made namely control beam without additional GFRP sheets, beam with 2 layer GFRP sheets without end anchorage, beam with 2 layer GFRP sheets with end anchorage type U-shape straps, fasteners and steel bolts. Each group consists of 3 specimens. The data observed during the test are cracking loads, crack patterns, crack widths, ultimate load capacities, deflections and failure modes. Test results show that end anchorage changes starting point of de-bounding mode failure of the GFRP sheets which is from the point of cut-off to the middle span of the beams. The addition of end anchorages can increase the ultimate flexural capacity of the beam with 2 layer GFRP sheet about 18.628%, 5.555% and 10.131% respectively for end anchorage of fastener, U-shape straps and steel bolts. When it is compared to the capacity of control beam, the ultimate flexural capacity of the beams with end anchorage is higher about 31.373%, 18.3% and 22.876% for end anchorage of fastener, U-shape straps and steel bolts, respectively.
Keywords: end anchorage, GFRP strengthening, reinforced concrete beam, flexural strength.